Crystal Structure of a Conserved Hypothetical Protein MJ0927 from Methanocaldococcus jannaschii Reveals a Novel Quaternary Assembly in the Nif3 Family. (28th August 2014) - Chen, Sheng-Chia; Huang, Chi-Hung; Yang, Chia Shin; Kuan, Shu-Min; Lin, Ching-Ting; Chou, Shan-Ho; Chen, Yeh
Abstract : A Nif3 family protein of Methanocaldococcus jannaschii, MJ0927, is highly conserved from bacteria to humans. Although several structures of bacterial Nif3 proteins are known, no structure representing archaeal Nif3 has yet been reported. The crystal structure of Methanocaldococcus jannaschii MJ0927 was determined at 2.47 Å resolution to understand the structural differences between the bacterial and archaeal Nif3 proteins. Intriguingly, MJ0927 is found to adopt an unusual assembly comprising a trimer of dimers that forms a cage-like architecture. Electrophoretic mobility-shift assays indicate that MJ0927 binds to both single-stranded and double-stranded DNA. Structural analysis of MJ0927 reveals a positively charged region that can potentially explain its DNA-binding capability. Taken together, these data suggest that MJ0927 adopts a novel quartenary architecture that could play various DNA-binding roles in Methanocaldococcus jannaschii .